2009
DOI: 10.1007/s00422-009-0358-x
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding an electronic integrate-and-fire circuit

Abstract: Many physical and biological phenomena involve accumulation and discharge processes that can occur on significantly different time scales. Models of these processes have contributed to understand excitability self-sustained oscillations and synchronization in arrays of oscillators. Integrate-and-fire (I+F) models are popular minimal fill-and-flush mathematical models. They are used in neuroscience to study spiking and phase locking in single neuron membranes, large scale neural networks, and in a variety of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
(24 reference statements)
1
17
0
Order By: Relevance
“…This paper is the third in a series of three on simulation models of cultured networks. Our two previous studies [26], [27] have shown that random recurrent network activity models generate intra- and inter-bursting patterns similar to experimental data. The networks were noise or pacemaker-driven and had Izhikevich-neuronal elements with only short-term plastic (STP) synapses (so, no long-term potentiation, LTP, or depression, LTD, was included).…”
supporting
confidence: 77%
“…This paper is the third in a series of three on simulation models of cultured networks. Our two previous studies [26], [27] have shown that random recurrent network activity models generate intra- and inter-bursting patterns similar to experimental data. The networks were noise or pacemaker-driven and had Izhikevich-neuronal elements with only short-term plastic (STP) synapses (so, no long-term potentiation, LTP, or depression, LTD, was included).…”
supporting
confidence: 77%
“…This has proven to be a remarkably good approximation to the Hodgkin-Huxley model if spike duration times are short compared to interspike times (Knight 1972;Dayan and Abbott 2001;Carrillo and Hoppensteadt 2010). Equation (16) is to be solved under the condition that x is reset to rest, x = 0, on firing a spike, x = 1, a non-linear framework.…”
Section: Leaky-integrate-and-fire Modelmentioning
confidence: 98%
“…with firing threshold x = 1 and resting state x = 0, has proven a trustworthy approximation when the input timescale is large compared to the duration of the action potential (Knight, 1972;Keener & Sneyd, 1998;Dayan & Abbott, 2001;Carrillo & Hoppensteadt, 2010). Equation 2.7 models the activity of the membrane by an RC circuit where 纬 represents leakage conductance and s is the input current.…”
Section: Formulationmentioning
confidence: 98%